Medium-Term Debt Management Strategy : Analytical Tool Manual - Balibek, Emre (Technical Notes and Manuals; Technical Notes and Manuals ;, 2019)
This report provides guidance on using the Analytical Tool of the Medium-Term Debt Management Strategy (MTDS). The MTDS framework consists of a methodology, published as the 'Guidance Note for Developing a Medium-Term Debt Management Strategy', and an associated analytical tool (AT) that can be used to assess the cost-risk trade-offs of alternative strategies to help identify the preferred strategy. The MTDS framework supported by the AT quantitative analysis helps to determine the financing strategy. The chosen debt management strategy sets out the financing composition path to meet the debt management objective(s). The profile of future interest payments and the amortizations of new debt are driven by the debt management strategy. The MTDS AT is based on annual cash flow. Although this assumption is enough for analyzing alternative debt management strategies, in some cases, particularly for countries that are heavily dependent on short-term securities with maturities of less than a year, it would be helpful to work with cash flows with higher frequency.